Robotic‐assisted diaphragmatic plication: Improving safety and effectiveness in the treatment of diaphragmatic paralysis. Issue 3 (24th January 2022) - Lampridis, Savvas; Pradeep, I. H. D. Saman; Billè, Andrea
Abstract: Background: Diaphragmatic plication can be performed with various surgical approaches. The aim of this study was to assess the safety and effectiveness of robotic‐assisted plication. Methods: We retrospectively reviewed consecutive patients who underwent diaphragmatic plication from 2017 to 2021. Results: Eighteen patients underwent 20 operations, 11 of which were performed with robotic‐assisted thoracoscopic surgery (RATS) and 9 with open transthoracic approach. RATS was associated with shorter operating time (80 vs. 120 min; p  = 0.04), less blood loss (20 vs. 100 ml; p  = 0.01), shorter chest‐drain duration (1 vs. 3 days; p  = 0.01), and shorter length of stay (3 vs. 7 days; p  = 0.04). The median grade in the Medical Research Council dyspnoea scale improved from four to two in both groups. Conclusions: Robotic‐assisted diaphragmatic plication is a safe procedure that can significantly improve dyspnoea and is associated with shorter hospitalisation compared to open approach.